Posterior Reversible Encephalopathy Syndrome: Utility of Fluid-attenuated Inversion Recovery MR Imaging in the Detection of Cortical and Subcortical Lesions - Casey, Sean O.; Sampaio, Ricardo C.; Michel, Eduard; Truwit, Charles L. (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Posterior reversible encephalopathy syndrome (PRES) is typically characterized by headache, altered mental functioning, seizures, and visual loss associated with imaging findings of bilateral subcortical and cortical edema with a predominantly posterior distribution. Our goal was to determine whether fluid-attenuated inversion recovery (FLAIR) imaging improves the ability to detect subtle peripheral lesions of PRES, as compared with conventional MR techniques.METHODS: Sixteen patients with clinical and imaging findings consistent with PRES were studied. Thirteen patients had undergone transplantation and had cyclosporin A neurotoxicity. Fast-FLAIR images were compared with spin-echo proton density–and T2-weighted images.RESULTS: FLAIR imaging improved diagnostic confidence and conspicuity of the T2 hyperintense lesions of PRES, typically in the subcortical white matter of the parietooccipital regions bilaterally. On all 23 abnormal MR studies, FLAIR was judged superior to proton density–and T2-weighted images for the detection of PRES in the supratentorial brain. In a mean of 6.7 of 23 studies, FLAIR findings prompted a raise in the grade of disease severity. FLAIR also showed cortical involvement in 94% of patients with PRES and in a mean of 46% of the total lesion burden. In four cases, subtle lesions were virtually undetectable without FLAIR. Brain stem or cerebellar disease was encountered in 56% of patients.CONCLUSION: FLAIR improves the ability to diagnose and detect subcortical and cortical lesions in PRES as compared with proton density–and T2-weighted spin-echo images. We therefore believe that FLAIR should be performed in patients with suspected PRES to allow more confident recognition of the often subtle imaging abnormalities.